2020
DOI: 10.1016/j.vas.2020.100120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between rectal and body surface temperature in dogs by the calibrated infrared thermometer

Abstract: Highlights Dogs poorly tolerate rectal temperature measurements with a contact thermometer. Existing alternative approaches used uncalibrated infrared thermometers. Gum and inguinal temperature are correlated moderately to rectal temperature. Hyperthermia was detected with sensitivity and specificity up to 90.0% and 78.6%. Future studies should include a calibrated thermometer and control external factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Infrared auricular thermometers have been developed to solve problems regarding BT measurements in humans and dogs [ 2 - 4 , 6 - 8 ]. Although some studies have reported a strong correlation between rectal and auricular BT in dogs [ 2 , 3 , 6 , 7 ], others have found only a slight correlation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared auricular thermometers have been developed to solve problems regarding BT measurements in humans and dogs [ 2 - 4 , 6 - 8 ]. Although some studies have reported a strong correlation between rectal and auricular BT in dogs [ 2 , 3 , 6 , 7 ], others have found only a slight correlation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have reported a strong correlation between rectal and auricular BT in dogs [ 2 , 3 , 6 , 7 ], others have found only a slight correlation [ 4 ]. Gum temperature can be a good predictor of rectum temperature [ 8 ], but this technique, despite its several advantages, still requires close contact to the animals, with the risk of disturbance and disease transmission [ 5 ]. Infrared surface temperature (ST), as a non-contact technique with real-time results and minimal time and labor consumption, is measured based on the radiation heat loss in the infrared range [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For healthy dogs, body surface temperature, as measured by thermography, is approximately 30–35 °C [ 24 ]. In addition, thermographic readings are lower than rectal temperature [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For healthy dogs, body surface temperature, as measured by thermography, is approximately 30–35 °C [ 24 ]. In addition, thermographic readings are lower than rectal temperature [ 24 ]. Even in studies investigating body surface temperature after exercise, the increase is only approximately 1 °C [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, TIT is increasingly used (CUGMAS et al, 2020). This technology involves use of pyroelectric sensors to detect the heat emanating from the tympanic membrane and inner surface of the external ear canal to obtain a more accurate measurement of core body temperature (FRADEN, 1991).…”
Section: Introductionmentioning
confidence: 99%